Physicomechanical Properties of Tissue Conditioner Reinforced with Glass Fibers - Aftab Ahmed Khan; Abdulaziz Abdullah AlKhureif; Eraj Humayun Mirza; Raghad Khalid AlHassoun; Aisha Wasi; Jukka Matinlinna (Bioengineering)
Tissue conditioners are temporary lining materials applied to dentures to soothe and cushion inflamed or traumatized oral tissues, typically resulting from ill-fitting dentures. This laboratory study aimed to evaluate the physicomechanical properties of a clinical tissue conditioner with 0.5 and 1 wt.% of silanized, micron-sized, E-glass fibers. The experimental tissue conditioners were characterized based on their molecular structure, surface roughness, contact angle, tensile strength, dimensional stability, water sorption, and solubility. The results were analyzed by two-way ANOVA (factors: material composition and aging) and the post hoc Tukey’s test. FTIR analysis revealed characteristic peaks at 1710–1720 cm−1, 2800–3000 cm−1, and 1400 cm−1, indicating a strong interaction between the tissue conditioner and the micron-sized glass fibers. Tensile strength was highest at baseline but declined in all groups after 14 days of aging, with the 0.5 wt.% glass fiber group showing the least reduction. Linear dimensional changes remained consistent across all groups. Surface roughness increased in all groups after 14 days, though the 0.5 wt.% glass fiber group exhibited the smallest increase. Water contact angles ranged from 71° to 92°, suggesting adequate surface wettability for clinical use. The experimental groups consistently demonstrated lower water sorption and solubility values. The 0.5 wt.% glass fiber formulation showed the potential to improve clinical performance by its reduced water sorption and solubility. However, long-term studies and clinical trials are necessary to validate the clinical effectiveness of this formulation.